Systematic Review: Potential of Curcumin Compounds as Immunostimulants in the Prevention of SARS-CoV 2 Virus - Ma’arif, Burhan; Suryanto, Suryanto; Lestari, Arianti; Batrisyia, Asna Defi (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2021)
Curcumin is a compound from the turmeric rhizome plant ( Curcuma longa ), which has immunostimulating activity. This activity has been tested pre-clinically in vitro , in vivo , and in silico . It can be used as raw material for drugs in the development of new drugs to prevent the SARS-CoV 2 virus. The purpose of this study was to examine the immunostimulatory activity of turmeric  in vitro ,  in vivo , and  in silico and to explore the mechanism of curcumin compounds as immunostimulants. The method used in this systematic review is Systematic-Meta Analysis by identifying articles from several journal databases (Google Scholar, ResearchGate, ScienceDirect, and Garuda Dikti). Furthermore, the article selection process used a PRISMA guideline flow chart. This process found 15 articles as the main reference, five articles containing in vitro research, five in vivo , and five in silico from the turmeric rhizome plant. In vitro, preclinical tests show that curcumin compounds have an immunostimulating effect characterized by the occurrence of proliferation and activation in several types of immune system cells. In vivo study was proven by increased phagocytic activity and increased leukocyte production in experimental animals. Whereas in silico was demonstrated by the binding of various SARS-CoV 2 receptors.